Antioxidants as a Potential Target against Inflammation and Oxidative Stress in Attention-Deficit/Hyperactivity Disorder - Lourdes Alvarez-Arellano; Nadia González-García; Marcela Salazar-García; Juan Carlos Corona (MDPI AG, 2020)
Psychostimulants and non-psychostimulants are the medications prescribed for the treatment of attention-deficit/hyperactivity disorder (ADHD). However, several adverse results have been linked with an increased risk of substance use and side effects. The pathophysiology of ADHD is not completely known, although it has been associated with an increase in inflammation and oxidative stress. This review presents an overview of findings following antioxidant treatment for ADHD and describes the potential amelioration of inflammation and oxidative stress using antioxidants that might have a future as multi-target adjuvant therapy in ADHD. The use of antioxidants against inflammation and oxidative conditions is an emerging field in the management of several neurodegenerative and neuropsychiatric disorders. Thus, antioxidants could be promising as an adjuvant ADHD therapy.